2023
DOI: 10.15605/jafes.038.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Clinicodemographic Profile and Outcomes of Type 2 Diabetes Mellitus in the Indonesian Cohort of DISCOVER: A 3-Year Prospective Cohort Study

Abstract: Background. Indonesia is amongst the top 10 countries with the highest prevalence of Type 2 Diabetes Mellitus (T2DM) at 10.8%. However, the distinguishable features of T2DM in Indonesia remain obscure. Therefore, the DISCOVER study aimed to describe the characteristics of T2DM patients, associated vascular complications and treatment in Indonesia.Methodology. DISCOVER study is a multi-country, multicenter, prospective, cohort study over 3 years. In the present study, the data were collected from 13 sites from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Diabetes Melitus tipe 2 (DMT2) yang tidak ditangani secara tepat, akan mengakibatkan komplikasi yang serius pada penyandangnya (Papatheodorou et al, 2018). Sebanyak 32% pasien DM tipe 2 di Indonesia mengalami komplikasi neuropati perifer, 26,2% mengalami komplikasi makrovaskuler, dan 17,2% mengalami komplikasi mikrovaskuler (Soeatmadji et al, 2023). Komplikasi yang terjadi pada pasien DM juga dapat mengakibatkan timbulnya masalah baik dari segi fisik maupun psikologis.…”
Section: Pendahuluanunclassified
“…Diabetes Melitus tipe 2 (DMT2) yang tidak ditangani secara tepat, akan mengakibatkan komplikasi yang serius pada penyandangnya (Papatheodorou et al, 2018). Sebanyak 32% pasien DM tipe 2 di Indonesia mengalami komplikasi neuropati perifer, 26,2% mengalami komplikasi makrovaskuler, dan 17,2% mengalami komplikasi mikrovaskuler (Soeatmadji et al, 2023). Komplikasi yang terjadi pada pasien DM juga dapat mengakibatkan timbulnya masalah baik dari segi fisik maupun psikologis.…”
Section: Pendahuluanunclassified
“…It is now being utilized as an additional therapy for HF in Indonesia, and it has been proven to have antiarrhythmic features as well. The first SGLT-2 inhibitor cohort study in Indonesia was reported in DISCOVER study, where it was used in 1.2% of patients [4,5] . Despite inconsistent [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of diabetes is projected to increase dramatically, with estimates suggesting that approximately 642 million individuals will be affected by the year 2040 [2]. Recent data positions Indonesia as the sixth country with the highest number of DM cases among those aged 15 years and older, with a reported prevalence of 10.8% [3]. The increasing prevalence of DM, particularly type 2 diabetes mellitus (T2DM), poses a significant burden on healthcare systems and highlights the need for effective management strategies.…”
Section: Introductionmentioning
confidence: 99%